Coefficient Estimates of a New Subclass of Biunivalent Functions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we try to extend and obtain some more results inspired by P. Goswami and Aljouiee [9]. Here we are introducing a new subclass of biunivalent functions by using q-derivative operator, quasi-subordination and convolution analytic bi-univalent functions. Also we find both some initial and general coefficient bounds.